2022
DOI: 10.1108/ci-05-2022-0114
|View full text |Cite
|
Sign up to set email alerts
|

The DAWN readiness model to assess the level of use of Industry 4.0 technologies in the construction industry in Brazil

Abstract: Purpose Construction industry (CI) has great prominence for the world economy, and it is expected that, with the use of the innovative technologies and approaches of Industry 4.0 (I4.0), the new industrial paradigm, construction can reach higher levels of productivity. This study aims to develop a model (readiness model) to assess the level of use of I4.0 technologies by the construction sector in Brazil and its most relevant applications. Design/methodology/approach The methodology used was bibliographic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 79 publications
(133 reference statements)
0
2
0
Order By: Relevance
“…Nowadays the manufacturing industry is experiencing intense competition with dynamic markets, globalization, dynamic demands and the like. To face such a challenge, adaptable, efficient and flexible production systems are indispensable and the fourth industrial revolution or Industry 4.0 as it is also named, promotes modern technological solutions Ribeiro et al (2022), that stand out from the rigid manufactures of today, by allowing flexibility and scalability of production lines (Contador et al, 2020;Hamzeh et al, 2018;Satyro et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nowadays the manufacturing industry is experiencing intense competition with dynamic markets, globalization, dynamic demands and the like. To face such a challenge, adaptable, efficient and flexible production systems are indispensable and the fourth industrial revolution or Industry 4.0 as it is also named, promotes modern technological solutions Ribeiro et al (2022), that stand out from the rigid manufactures of today, by allowing flexibility and scalability of production lines (Contador et al, 2020;Hamzeh et al, 2018;Satyro et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to frameworks and concept definition, previous research has shown that the transformation of the construction industry toward Construction 4.0 can result in increased productivity, improved quality, greater added value, better sustainability indexes, optimization of natural resources, reduction of waste, and better safety conditions for workers [6][7][8][9][10]. However, profound changes are needed throughout the design and construction process and its stakeholders to successfully introduce the innovative technologies reported in the literature [6,7,[10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%